PERAN BAGIAN PERTANAHAN PEMERINTAH KABUPATEN MALANG DALAM RANGKA PENYELESAIAN SENGKETA TANAH SECARA MEDIASI - Chusnul Chotimah (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract The problem in the area of land not just about the issue of ownership and the rule of law, but it is also a problem in politics. By doing so, then problem arise about: